Theoretical investigation of catalytic n-butane isomerization over H-SSZ-13 - Lucas Spiske; Philipp N. Plessow; Kamila Kazmierczak; Bart D. Vandegehuchte; Felix Studt (Frontiers in Catalysis, 2023)
Hybrid density functional theory calculations are used to investigate different mechanisms of the isomerization of n-butane to isobutane via intermediate formation of olefins. The monomolecular mechanism for isomerization of butene and isobutene is found to be prevalent, with a Gibbs free energy barrier of 155 kJ/mol at 400°C, compared to the bimolecular mechanism (190 kJ/mol) due to less favorable entropy for the latter. Hydrogen transfer reactions that convert olefins into alkanes (and vice versa) are also included in the investigations, and show a free energy barrier of 203 kJ/mol for conversion of isobutene to isobutane. Additionally, a methyl transfer mechanism is discussed as a possible pathway for formation of C3 and C5 side products, in comparison to the bimolecular mechanism; the highest barrier of the initial methyl transfer is calculated to be 227 kJ/mol. We discuss the influence of entropy and anharmonicity on all mechanisms, stating that through the uncertainties in computational methods when calculating these systems, the calculated reaction barriers are likely to be overestimated here.